Health system-related needs for healthy nutritional behaviors in adolescent girls with polycystic ovary syndrome (PCOS): a qualitative study in Iran - Leila Hajivandi; Mahnaz Noroozi; Firoozeh Mostafavi; Maryam Ekramzadeh (BMC, 2022)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women. Given the prevalence of this disease in adolescent girls as well as its serious physical, psychological, and social consequences, the present study aimed to explore the health system-related needs for healthy nutritional behaviors in adolescent girls with PCOS. Methods This qualitative content analysis was conducted in Shiraz, Iran between November 2016 and October 2017. Eighteen Adolescent girls with PCOS and 15 healthcare providers (midwives, gynecologists, nutritionists, and endocrinologists) were selected through purposeful sampling with maximum variation strategy. Data were collected through individual in-depth and semi-structured interviews, focus group discussions, and field note, and simultaneously analyzed using the conventional qualitative content analysis method. Results Three main categories that appeared included: 1) education and counseling on healthy nutrition and support for adolescent girls with PCOS with sub-categories of "empowering adolescent girls with PCOS to adopt healthy nutritional behaviors", "providing services and education about healthy nutritional behaviors as a team", and "the health team attention to the concerns of adolescent girls with PCOS and closely following the disease status, 2) solving communication problems with sub-categories of "proper interactions and building trust between health team members and adolescent girls" and "proper interactions between members of the health team", and 3) developing the optimal structure for providing health services with sub-categories of "solving problems related to human resources, "promoting the position of health issues related to adolescent girls in the health system", and "promoting policy-making in the field of nutritional health of adolescent girls". Conclusions Based on the results of the present study, necessary measures should be taken to educate and advise on healthy nutrition, and to support adolescent girls with PCOS. The desired structure should also be developed to provide health services to these girls. By solving communication problems and building trust between the members of the health team and these girls, one can guide them to adopt healthy nutritional behaviors.